(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The development of nano-enhanced soap offers a groundbreaking approach to enhancing the physicochemical and antimicrobial attributes of conventional soaps. This study compared the prepared soap with two commercially available soaps, examining parameters such as physicochemical properties, antimicrobial efficacy, and minimum inhibitory and bactericidal concentrations. The physicochemical analysis indicated that the prepared soap met regulatory standards for pH, solubility, hardness, and total fatty matter (TFM), confirming its suitability for human use. Specifically, the produced soap exhibited the following properties: pH = 6.30±0.02, Hardness = 1.3±0.02 cm, Foamability = 6.9±0.02 cm, Solubility = 80±0.02 s, and Total Fatty Matter (TFM) = 55±2%. Despite slightly reduced foamability due to the absence of foam enhancers, the prepared soap retained effective cleaning capabilities. Antimicrobial testing using the disc diffusion method demonstrated the soap’s broad-spectrum activity against Gram-positive and Gram-negative bacteria, as well as fungal species, with efficacy increasing in a concentration-dependent manner. Unlike the two commercially available soaps used for comparison, which each exhibited high activity against specific pathogens, the prepared soap consistently inhibited all tested pathogens. This broad-spectrum activity highlights the superior antimicrobial properties of the prepared soap. It exhibited a minimum inhibitory concentration (MIC) of 50 mg/L and a minimum bactericidal concentration (MBC) of 100 mg/L for all pathogens, outperforming the commercially available soaps. Overall, the prepared soap demonstrated enhanced physicochemical characteristics and balanced antimicrobial efficacy, positioning it as a versatile hygiene product capable of addressing a wide range of microbial infections. Its wide-spectrum activity against all pathogens and superior physicochemical properties underscore...